Humanization of bone and bone marrow in an orthotopic site reveals new potential therapeutic targets in osteosarcoma. (July 2018) - Wagner, Ferdinand; Holzapfel, Boris M.; McGovern, Jacqui A.; Shafiee, Abbas; Baldwin, Jeremy G.; Martine, Laure C.; Lahr, Christoph A.; Wunner, Felix M.; Friis, Thor; Bas, Onur; Boxberg, Melanie; Prodinger, Peter M.; et al.
Abstract: Background: Existing preclinical murine models often fail to predict effects of anti-cancer drugs. In order to minimize interspecies-differences between murine hosts and human bone tumors of in vivo xenograft platforms, we tissue-engineered a novel orthotopic humanized bone model. Methods: Orthotopic humanized tissue engineered bone constructs (ohTEBC) were fabricated by 3D printing of medical-grade polycaprolactone scaffolds, which were seeded with human osteoblasts and embedded within polyethylene glycol-based hydrogels containing human umbilical vein endothelial cells (HUVECs). Constructs were then implanted at the femur of NOD- scid and NSG mice. NSG mice were then bone marrow transplanted with human CD34  +  cells. Human osteosarcoma (OS) growth was induced within the ohTEBCs by direct injection of Luc-SAOS-2 cells. Tissues were harvested for bone matrix and marrow morphology analysis as well as tumor biology investigations. Tumor marker expression was analyzed in the humanized OS and correlated with the expression in 68 OS patients utilizing tissue micro arrays (TMA). Results: After harvesting the femurs micro computed tomography and immunohistochemical staining showed an organ, which had all features of human bone. Around the original mouse femur new bone trabeculae have formed surrounded by a bone cortex. Staining for human specific (hs) collagen type-I (hs Col-I) showed human extracellular bone matrix production. The presence of nuclei staining positive for human nuclear mitotic apparatus protein 1 (hs NuMa) proved the osteocytes residing within the bone matrix were of human origin. Flow cytometry verified the presence of human hematopoietic cells. After injection of Luc-SAOS-2 cells a primary tumor and lung metastasis developed. After euthanization histological analysis showed pathognomic features of osteoblastic OS. Furthermore, the tumor utilized the previously implanted HUVECS for angiogenesis. Tumor marker expression was similar to human patients. Moreover, the recently discovered musculoskeletal gene C12orf29 was expressed in the most common subtypes of OS patient samples. Conclusion: OhTEBCs represent a suitable orthotopic microenvironment for humanized OS growth and offers a new translational direction, as the femur is the most common location of OS. The newly developed and validated preclinical model allows controlled and predictive marker studies of primary bone tumors and other bone malignancies.